Toxicity of essential oils on cabbage seedpod weevil (Ceutorhynchus obstrictus) and a model parasitoid (Nasonia vitripennis) - Sulg, Silva; Kaasik, Riina; Kallavus, Triin; Veromann, Eve (Frontiers in Agronomy, 2023)
Plant essential oils are being increasingly studied as a potential environmentally friendly alternative to synthetic insecticides. The insecticidal efficacy of essential oils on cabbage seedpod weevil (Ceutorhynchus obstrictus), an important oilseed rape pest, has not been previously tested. We examined the impact of six essential oils on C. obstrictus via contact with dry residues on leaf and flower surfaces. We also examined the effect of these essential oils on a model non-target parasitoid wasp, Nasonia vitripennis. Exposure to dry residues of cumin (Cuminum cyminum) and cinnamon (Cinnamomum verum) essential oils (applied to oilseed rape leaves) resulted in significant loss of mortality and immobility of C. obstrictus adults. Treatment with C. cyminum essential oil at 1.5% resulted in 50.71% mortality and 87.3% combined mortality and immobility in C. obstrictus. Treatment with C. verum oil at 1.5% concentration resulted in 90% mortality and 88.8% mortality and immobility in C. obstrictus. All treatments with studied essential oil dry residues at 0.3% concentration caused high mortality and immobility on N. vitripennis. The greatest mortality and immobility was observed at 0.3% concentration in F. vulgare and C. verum treatments (54 and 53% loss respectively). At 0.1% concentration, F. vulgare and T. vulgaris reduced significantly parasitoids mobility and at 1.5% concentration all essential oils resulted in 100% mortality of N. vitripennis after 3 h. Our study revealed that C. cyminum and C. verum essential oils may have potential in the management of C. obstrictus. However, their impact on non-target organisms, including parasitoids, needs to be studied more thoroughly to determine the potential of essential oil main compounds in integrated pest management.